Planning, collaboration, innovation: three keys to get a good university teaching practice - Carmen Álvarez Álvarez; Gonzalo Silió Sáiz; Elia Fernández Díaz (Universitat Politècnica de València, 2012)
This article proposes three fundamental aspects to get a good university teaching practice: planning, collaboration and innovation. A purpose of the design process, curriculum development and innovation developed by three teachers of the subject " School Organisation" pertaining to the curriculum of Teacher Training at the University of Cantabria, the text explores these three issues. Educational planning process around the definition of a shared procedural principles and the ongoing collaborative work of teachers around them, has enabled the development of a material adapted to the requirements of the European Space of Higher Education where a flexible, open and predisposed attitude to the improvement has been present at all everytimes: in the classroom, trying to promote spaces for dialogue ("agora") between teachers and students in a lecture series on School Organization developed in our ability to expand on the subject references and employing new technologies, unquestionable allies in the process. The results of our teaching and assessment of the subject make it clear that the process followed in this matter has been well received by students. Therefore, we conclude that it is very important to establish mechanisms for design, development and innovation to try to facilitate communication between those involved from the planning, seeking cooperative work and educational innovation.